2022
DOI: 10.1002/hyp.14487
|View full text |Cite|
|
Sign up to set email alerts
|

Saturated hydraulic conductivity of boreal peat and its relationships with peat properties and sampling depth

Abstract: The boreal region is a significant peat‐forming area. With peat, there lie other natural resources, including mineral ores and fossil fuels needed by our economy. However, mining for mineral resources or any other activity that leads to large‐scale groundwater extraction in the near vicinity or underneath the mires can alter the water levels in the overlaying ecosystems and thus have a damaging effect on them, raising concerns about the mires' preservation. Peat itself may isolate surface vegetation from drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 35 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Mires in the Tomsk region (Dyukarev & Pologova, 2011; Kopysov et al, 2020) with thicker peat deposits have been reported to be more resistant to the vertical drainage. The hydraulic conductivity can vary by several orders of magnitude, even for the same peat type (Morris et al, 2022; Paat et al, 2022). Direct measurements and indirect estimates show that the lowest conductivity values in raised bogs of northeastern Estonia occur near the bottom of the peat column in highly decomposed ( von Post score H7‐H10) peats formed at the fen and transitional mire growth stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mires in the Tomsk region (Dyukarev & Pologova, 2011; Kopysov et al, 2020) with thicker peat deposits have been reported to be more resistant to the vertical drainage. The hydraulic conductivity can vary by several orders of magnitude, even for the same peat type (Morris et al, 2022; Paat et al, 2022). Direct measurements and indirect estimates show that the lowest conductivity values in raised bogs of northeastern Estonia occur near the bottom of the peat column in highly decomposed ( von Post score H7‐H10) peats formed at the fen and transitional mire growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurements and indirect estimates show that the lowest conductivity values in raised bogs of northeastern Estonia occur near the bottom of the peat column in highly decomposed ( von Post score H7‐H10) peats formed at the fen and transitional mire growth stages. The hydraulic conductivity of those layers may be as low as 10 −10 to 10 −8 m/s (Paat et al, 2022). However, the thickness of the layer, in unison with its conductivity, determines whether it can effectively limit vertical infiltration rates to a level that would be lower from the leftover precipitation after evapotranspiration or fully isolate aquifers above and below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(K oed ). The oedometer ring permeameter test results can be found in the separately provided dataset (Paat et al, 2024). It seems that in Kaasiksoo, the determined K v values for bottommost fen peat are an order of magnitude higher than measured in the laboratory…”
Section: Peat Compressibility and Vertical Hydraulic Conductivitymentioning
confidence: 95%
“…The dried and weighed peat samples were then ground using a pestle and mortar for humification determination. Humification was chosen instead of the more commonly used von Post score to describe the degree of decomposition, as it is a more objective measuring technique and has shown a good correlation with peat's saturated hydraulic conductivity values(Paat et al, 2022).The separately collected 0.5 m interval peat samples were utilized to determine compressibility and vertical hydraulic conductivity through permeameter tests. Compressibility of the collected peat samples was assessed using standard oedometer tests (ISO 17892-5, 2017) with a Matest S260 front-loaded oedometer.…”
mentioning
confidence: 99%